1997
DOI: 10.1111/j.1751-1097.1997.tb01908.x
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation of DNA with 193 nm Light Yields Formamidopyrimidine‐DNA Glycosylase (Fpg) Protein‐Sensitive Lesions

Abstract: Irradiation of aqueous solutions of plasmid DNA (pUC18) at pH 7.6 with 193 nm laser light results in low yields of prompt single strand breakage (air-saturated sample phi ssh = [1.5 +/- 0.1] x 10(4), argon-saturated sample phi ssh = [0.9 +/- 0.1] x 10(4). Treatment of the irradiated DNA samples with Escherichia coli formamidopyrimidine-DNA glycosylase (Fpg) protein results in an approximate 20-fold increase in the yield of single strand break-age (air-saturated sample phi fpg = [33.1 +/- 3.1] x 10(-4), argon-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Our results, therefore, reinforce the hypothesis that laser-induced effects on E. coli cells would occur by free radical generation at sub-lethal level. Induction of DNA lesions by ultraviolet lasers (193,248,254, and 266 nm), at continuous wave and pulsed emission modes, has been used in different plasmids [40][41][42][43][44], and also treatment of herpes simplex keratitis with excimer laser application [45]. The discrepancy between the results of Hawkins and Abrahamse [46], who reported induction of DNA lesions by He-Ne red laser (632.8 nm), and ours is that a lower dose (8 J/cm 2 ) and a different wavelength (658 nm) was used.…”
Section: Discussionmentioning
confidence: 99%
“…Our results, therefore, reinforce the hypothesis that laser-induced effects on E. coli cells would occur by free radical generation at sub-lethal level. Induction of DNA lesions by ultraviolet lasers (193,248,254, and 266 nm), at continuous wave and pulsed emission modes, has been used in different plasmids [40][41][42][43][44], and also treatment of herpes simplex keratitis with excimer laser application [45]. The discrepancy between the results of Hawkins and Abrahamse [46], who reported induction of DNA lesions by He-Ne red laser (632.8 nm), and ours is that a lower dose (8 J/cm 2 ) and a different wavelength (658 nm) was used.…”
Section: Discussionmentioning
confidence: 99%
“…This is a consequence of the fact that guanine is the most easily oxidized of the nucleobases . Such damage can be caused by diverse oxidative processes including radiation, hole migrations from other nucleosides, and reactions with chemical oxidants . It has also been proposed that water molecules in the first hydration shell might catalyze the formation of tautormers with degenerative effects .…”
Section: The Problemmentioning
confidence: 99%
“…UV laser irradiation has been performed to study the effect of base ionization within DNA. The first studies focused on the delineation of modifying effects of vacuum UV (193 nm) on plasmid DNA (124)(125)(126). It was found that, like for Type I photosensitization, guanine was the most frequently damaged base, although cytosine, thymine and adenine were initially ionized upon exposure to laser pulses.…”
Section: Ionization Of Nucleobases By High-intensity Uvc Laser Pulsesmentioning
confidence: 99%